Identifying Performance Indicators for the Agriculture Sector in Developing Countries Through the ARDL Model : Special Reference of India - Singhal, Rahul; Gupta, Prateek; Singh, Ajay (Indian Journal of Finance, 2023)
Agriculture, the most prominent sector for a developing nation like India, is currently facing issues like low growth rate, inadequate finance, shifting of farmers from agriculture in the rural area to labor in the urban area, the lesser income of farmers, and lower contribution in GDP. The issues become more prominent when the agriculture sector accounts for more than half of the country’s workforce in India. In this research paper, an attempt was made to identify the most prominent performance indicators of the agriculture sector. A total of 11 indicators were explored in the study by applying the ARDL model. After analysis, four out of 11 indicators were identified as the most prominent indicators.